Brideshead revisited - Waugh, Evelyn, 1903-1966.; Gielgud, John, 1904-2000. (New York, N.Y. : Caedmon, 1981)
A story about the aristocratic Catholic family of Lord Marchmain, set in the period between World War I and World War II.
Automatic sequence.
Notes by Thomas Lask on container.
Read by Sir John Gielgud ; abridged and produced by Peter Orr.